E-COMMERCE APPLICATION AND BUSINESS PROFITS - Bushati, Brilanda; Gruda, Servete; Molla, Fatbardha (European Scientific Journal, ESJ, 2014)
This paper examines the main characteristics and bias behind the necessity of e-commerce in Albania, the socio-economic background of Albanian business and their readiness to support this new way of marketing. A survey and a subsequent analysis was conducted to examine organizations’ current practice on web-based information systems requirement. A typical ecommerce application consists of a network of texts, graphics, images, and so on, each of which should have one or more definite purposes that are part of the system development strategy. To determine important features that contribute to the success of the requirement analysis, it is important to find a theoretical relationship between e-commerce features and the development of e-commerce applications. Efforts were made to give answer to the question: “Can ecommerce be used by businesses in Albania? Are businesses in Albania ready and convenient for the advantages of e-commerce use? In order to examine the e-commerce development and the actual situation within Albanian territory the method of questionnaire was applied in some business organizations selected from the main cities –Tirana, Shkodra , Durres. Statistical methods help to analyze and determine the conclusions .The conclusion is that the trend of the Albanian business is to get all benefits out of e-commerce.